Tantangan Lokal Dan Global Kebijakan Politik Pendidikan Islam Di Indonesia - Roswida Sri Astuti; Qolbi Khoiri (Journal on Education, 2023)
This paper discusses local and global challenges to Islamic education political policies in Indonesia. This research method uses literature research or library research to be analyzed and concluded. In collecting data, the author uses literature study, namely research conducted by using data relating to the nature and objectives of education from journals, the internet and other relevant sources. The results of this study are: Globalization has a very large influence on the life of society, nation and state, in all aspects of life, be it social, political, cultural, religious or educational. The conclusion of this paper is that education must be designed in such a way as to enable students to develop the potential naturally and creatively in an atmosphere full of freedom, togetherness, and responsibility.